2015
DOI: 10.21608/jappmu.2015.52909
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Using Different Levels and Sources of Fats and Roughages on Productive Performance, Rumen Fermentation and Some Blood Parameters in Ruminant. 2: The Influence of Protected Fat as a Dietary Supplementation on Productive Performance of Ossimi Lambs.

Abstract: This study was conducted to investigate the effect of feeding different levels of protected fat on the digestion coefficients, nutritive value, ruminal and some blood parameters, and productive performance of Ossimi lambs. Three levels of protected fat (0, 4 and 8%) were used to cover 0, 10.80 and 19.98% of the total energy of the formulated rations, respectively. Twenty four Ossimi lambs averaging initial live body weight of 32.39±0.63 kg and aging 5-6 months were chosen and divided into three similar groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…The cows supplemented with organic zinc had better returns compared to inorganic zinc supplementation and control, which is likely to be achieved in the commercial conditions where organic zinc supplementation are reported to be used in the cows yielding milk to overcome the zinc deficiency by increasing the bioavailability compared to inorganic zinc supplementation. Similarly, Shakweer et al, (2010) reported that feed cost/kg milk produced (1.11) decreased with added zinc methionine when compared to the control group (1.17). The economical return was more prominent with diet contained zinc methionine (12.96) than the control (9.86) other treatment ration (10.54).…”
Section: Resultsmentioning
confidence: 88%
“…The cows supplemented with organic zinc had better returns compared to inorganic zinc supplementation and control, which is likely to be achieved in the commercial conditions where organic zinc supplementation are reported to be used in the cows yielding milk to overcome the zinc deficiency by increasing the bioavailability compared to inorganic zinc supplementation. Similarly, Shakweer et al, (2010) reported that feed cost/kg milk produced (1.11) decreased with added zinc methionine when compared to the control group (1.17). The economical return was more prominent with diet contained zinc methionine (12.96) than the control (9.86) other treatment ration (10.54).…”
Section: Resultsmentioning
confidence: 88%